Dynamic acoustic emission analysis of polymer electrolyte membrane fuel cells. (30th March 2022) - Bethapudi, V. S.; Hinds, G.; Shearing, P. R.; Brett, D. J. L.; Coppens, M.-O.
Abstract : This study measures acoustic activity from a PEM fuel cell as a dynamic response during potentiostatic and galvanostatic operations of the cell. Abstract : The acoustic emission (AE) technique has been demonstrated as a non-invasive and non-destructive water management diagnostic tool for polymer electrolyte membrane fuel cells (PEMFCs). AE probes the dynamics of water generation and removal at the flow-field of a PEMFC to establish the hydration state inside the cell and has been utilised to electro-acoustically characterise the performance of a PEMFC under different operating conditions. In this study, the dynamic relationship between the acoustic activity and the rate of electrochemical reaction inside a PEMFC is explored by correlating AE from PEMFCs with their performance using different time-based characterisations (polarisation scans at 10 s, 60 s, and 120 s voltage stabilisation durations). Flooding resulted in ∼16% decrease in maximum current density generated at 60 s and 120 s conditions compared to that at 10 s. Besides, flooding at longer durations is confirmed by acoustic emission as a function of polarisation (AEfP) and electrochemical impedance spectroscopy measurements. The effectiveness of the AE technique as a direct water diagnostic tool for PEMFCs is established through forward-reverse polarisation scans. Here, the AE energy generated during cell polarisations is utilised in understanding the water uptake and release mechanism inside the fuel cell. Furthermore, cell durability testing is performed through galvanostatic and potentiostatic measurements, where a synchronous relationship between the cell performance and the measured AE is identified.